System Development: What, Why, When And How CASE Tools Should Support Novice Software Engineers. - Sulaiman, Shahida; Khader, Ahmad Tajudin; Zainol, Zurinahni (2007)
Novice software engineers particularly computer science students need to be trained with theoretical knowledge and practical skills in system developments. The knowledge and skills may encompass the activities involve in all phases of system development including analysis, design, coding, testing and maintenance.